Sales and service for the wine professional - Julyan, Brian K. (Australia : South Western Cengage Learning, 2008)
In the new edition of Sales and Service for the Wine Professional Brian Julyan provides a comprehensible and in-depth coverage of the wine industry and continues to promote the highest standards of wine service and product knowledge. The text contains fully revised and up-to-date chapters to reflect the changing nature of the wine industry: an expanded chapter on viniculture and vinification, an updated and expanded chapter on the wines of the 'New World' and a new chapter on country-specific changes in legislation and licensing law.
1. Preparation and maintenance of bar and cellar -- 2. Viticulture and vinification --3. Wine controls, regulations and labelling -- 4. Sensory evaluation -- 5. Wine areas in the old world -- 6. Wine areas in the new world -- 7. Sparkling wines -- 8. Fortified wines -- 9. Spirits, beers and other drinks -- 10. Taking beverage orders -- 11. Table and bar service -- 12. Maintaining and increasing sales -- 13. Standard practices and behavior -- 14. Hygiene, health and safety
Includes index.
Keywords: WINE AND WINE MAKING; WINE SERVICE; BARTENDING